Social Media Marketing Activities and Brand Trust: Driving Loyalty in Indonesian’s MSMEs Fashion Brand - Maulasena, Mirza Fawwaz; Rahayu, Agus; Dirgantari, Puspo Dewi; Azatovich, Ablatdinov Sultanbek; Muradovna, Khudayarova Mekhrangiz (Universitas Pendidikan Indonesia, 2024)
This paper examines the impact of social media marketing activities (SMMa) on brand loyalty (BL) among followers of Indonesian micro, small, and medium enterprises (MSMEs) in the fashion sector. The increasing reliance on social media for brand engagement makes this topic particularly relevant, as businesses seek effective strategies to foster customer loyalty in a competitive landscape. The study investigates the relationship between SMMa, brand trust (BT), and BL, posing the research question: How do SMMa influence brand loyalty through brand trust in Indonesian MSME fashion brands? Utilizing a quantitative approach, data were collected through surveys distributed to followers of selected Indonesian MSME fashion brands, and structural equation modeling was employed for analysis. The findings reveal that SMMa significantly enhance brand trust, which in turn positively influences brand loyalty, highlighting the critical role of trust in the customer-brand relationship. The study concludes that Indonesian MSME fashion brands should prioritize trust-building strategies in their social media marketing efforts to cultivate customer loyalty, offering practical implications for marketers in the sector.